In vitro assessment of probiotic potential and safety of two Lactobacillus gasseri strains isolated from mother's breast milk and infant's feces in Vietnam - Viet Ha, Nguyen; Thuy Van, Pham Thi; Lan Anh, Hoang Thi; Thanh Trung, Trinh (Vietnam Journal of Biotechnology, 2023)
Probiotics have multiple beneficial effects on human health, including modulation of the immune system, inhibition of enteric pathogens, and prevention of metabolic disorders. Lactic acid bacteria (LAB) are the most common bacterial strains used for probiotic production. Among those, species belonging to the Lactobacillus acidophilus complex, especially L. gasseri, were well characterized and reported for probiotics. This study evaluated the potential probiotic characteristics of two L. gasseri strains (designed as VTCC 12791 and VTCC 12792) isolated from a pair of mother's breast milk and infant's feces. Both strains completely survived in the simulated gastric juice, highly tolerated the simulated intestinal juice (81-84%), strongly adhered to the HT-29 cell (23.5% for VTCC 12791 strain and 5.5% for VTCC 12792 strain), and had antagonistic activity against food-borne pathogens of Aeromonas dhakensis, Vibrio vulnificus, and Listeria monocytogenes, which demonstrated better beneficial properties than those of the commercial reference Lacticaseibacillus casei Shirota (LcS) strain. Additionally, both strains exhibited xanthine oxidase inhibitory activity (approximately 24%), which can lead to reducing serum uric acid. Regarding the safety aspect, the strains were sensitive to several antibiotics of ampicillin, vancomycin, tetracycline, chloramphenicol, erythromycin, and possessed alpha-hemolytic activity, which were similar to those of LcS strain. Our results suggested that L. gasseri VTCC 12791 and VTCC 12792 are potential candidates for producing probiotics and functional foods. Further in vivo studies are needed to prove their potential health benefits, especially in the treatment of hyperuricemia.